Big Data analysis of major elite sport events in the Netherlands. Case studies of the 2017 UEFA Women's Championship and the Rabo EuroHockey Championships 2017 - Hover, P.; Mol, P.-J.; Wassenaar, K. (2018 Malmö (Sweden), 5-8 September 2018, Managing Sport in a Changing Europe, 2018)
The growing usage of the internet, mobile devices and social media by an increasing number of people offers opportunities for investigating the web to explore and track interests, attitudes and preferences, including sport (events) related content. A substantial part of Dutch citizens are involved in following sport events, as spectators and via (online) media, which can also be witnessed in sport event related content in social media, blogs and other platforms, producing big data (Newcom.nl, 2018). Despite considerable governmental investments in the organisation of major sport events and measuring its social impact and a rapid development of social media management software, research on big data related to major sport events is very scarce. It was for this reason this explorative study on big data related to the 2017 UEFA Women's Championship and The Rabo EuroHockey Championships 2017, both held in the Netherlands, was developed. The aim of this study is threefold. Firstly, to assess the development of the level of online interest of these two elite sport events, measured in number of posts and their potential reach. Secondly, to evaluate the sentiment of these events by assessing the development of the ratio of positive, neutral and negative online content. In the third place, to reflect on the method and results and to appoint strengths and weaknesses.